Adaptation of the new multidimensional career insecurity scale (MU-CI-S) into the Indonesian language version - Luthfia Anisa; Tri Muji Ingarianti; May Elfina (Universitas Muhammadiyah Malang, 2025)
The adaptation of the new multidimensional career insecurity scale (MU-CI-S) measuring instrument aims to adjust the Indonesian cultural and language context, so that each item and dimension has standardized validity and reliability for further research in the context of workers in Indonesia. MU-CI-S is a measuring instrument developed and tested by previous researchers on workers in Germany and Switzerland. The use of career insecurity measurement tools with different cultural and linguistic backgrounds requires a series of adaptation processes based on the International Test Commission. Confirmatory Factor Analysis (CFA) was used to test the validity of the constructs and instruments that have been translated or modified to ensure the factor structure matches the data obtained. The study involved 379 employees in various industrial sectors in Indonesia. The analysis showed that the adapted scale model had a good fit with fit index parameters that met the standards (CFI = 0.965, TLI = 0.960. RMSEA = 0.048, SRMR = 0.029). Reliability tests with Cronbach's Alpha and Omega McDonald showed values above 0.80 on all dimensions, indicating that this scale is consistent in measuring career insecurity. In addition, convergent validity tested through the Average Variance Extracted (AVE) value shows results that meet the criteria (> 0.50), indicating that this scale is suitable for use in further research in Indonesia.